Variations of polyphenols, sugars, carotenoids, and volatile constituents in pumpkin (Cucurbita moschata) during high pressure processing: A kinetic study. (June 2022) - Dhenge, Rohini; Rinaldi, Massimiliano; Ganino, Tommaso; Santi, Saverio; Ferrarese, Irene; Dall'Acqua, Stefano
Abstract: High pressure processing (HPP) is an attractive technology for the preservation of vegetables with health promoting properties such as pumpkins. In this study pumpkin cubes were treated at six different pressures (100 to 600 MPa) at 20 °C for 3 min. Polyphenols (extracted both with solvent and by squeezing the residual material), carotenoids, sugars, and volatiles were evaluated. HPP at medium pressures (200–400 MPa) resulted in higher number of extractable polyphenols. Total sugars in HPP-treated samples were overall declining with increasing pressure. The total amount of carotenoids was higher in samples treated at lower pressures (100–300 MPa) and in the one at 600 MPa compared to untreated ones. Regarding volatile compounds, significant changes were observed for some aldehydes that increase after HPP application. This study revealed that treatment with intermediate pressure could ensure a higher amount of "availability" of polyphenols, carotenoids, volatiles, and total sugars in pumpkin samples. Highlights: Pumpkin cubes were treated at 6 different pressures (100 to 600 MPa) for 3 min Polyphenols, carotenoids, sugars, and volatiles were evaluated HPP treatments at 200 and 400 MPa showed the highest content of polyphenol Regarding volatile compounds HPP caused the increase of some aldehydes Total carotenoids were higher in samples treated at 100–300 MPa compared to control